Fé & Cia. LTDA: consumo religioso na sociedade contemporânea - Bastos, Edivaldo Correia (2007)
The present work is an exercise of analysis from the cultural exercises related to movie high one of its raised status more with the deity, the human being surrenders it Religion leaving puzzleds the prophets of its end. The purpose of this work is to show that the religious phenomenon is one of the essential components of the socialization human being. The religious dimension, although to have been kept out of society in modernity - it was cybernetics, is an indispensable compassing to guide the human being in the discovery of its true existencial direction. For this, to attenuate the legacy without appropriate title, overwhelming and despairing of the producing and consumer goods society, it is indispensable to add as basic part to the practical one of the religion. And this practice is specify at the acquirement as of commodities objects , than it is to they are consecrate, exercising um magical power under the assistants from the religion. The fair religious Expo Religious, like the Expo Crest (fair as of commodities and service of the Evangelist) and the one Expo Catholic (fair as of commodities and service of the Catholics), appears at the I initiate from the century 21 at the association Brazilian about to cater the litigation of the market religious at every their segments. The and objective of this research is bring forward those two fairs in the format as of Expo and your contribution at the dynamic from the religion crest at the association he acts